Signs of respect: embodying the train driver–signal relationship to avoid rail disasters. Issue 1 (2nd January 2017) - Rainbird, Sophia; Naweed, Anjum
Abstract: Train driving is a complex and dangerous activity. If a signal is passed at danger (SPAD), a driver experiences one of the most safety critical failure modes of rail. Train drivers are not only significantly emotionally and professionally impacted by SPADs that they have experienced; they are also affected by their potential occurrence. Using a mobilities approach, we identify SPAD risk reduction strategies that train drivers generate during dynamic interactive encounters with signals, between human/machine, time/space, structured movement/unstructured movement. Drivers form an intimate relationship whereby the signal is viewed with both reverence and contempt. Drivers anthropomorphise the signal, and predict SPAD potentiality aimed at outwitting the signal. We suggest that this human–signal interface offers new perspectives of SPADs, revealing that a signal means more than stop–caution–go.